Evaluation of the Quantitative Myasthenia Gravis Score and Grip Strength in Chinese Patients With Myasthenia Gravis: An Observational Study - Li, Jinghao; Weng, Senhui; Lin, Sen; Huang, Linwen; Yang, Xiaojun; Liang, Bo; Lu, Jiaxin; Jiang, Qilong (Frontiers in Neurology, 2021)
Introduction: The quantitative myasthenia gravis score (QMGS) is a commonly used scale for evaluating muscle weakness associated with myasthenia gravis (MG). It has been reported that some items used in the scale have low discriminative properties. However, there has been no research investigating the applicability of the QMGS in Chinese MG patients. In addition, the scoring method and ranges of grip strength items in QMGS need to be further evaluated. Methods: This study included 106 Chinese MG patients, enrolled between September 2020 and February 2021, who were evaluated using the QMGS. Each item in the QMGS was analyzed for distribution. Three methods of evaluating grip strength, grip strength decrement, maximum grip strength, and relative grip strength, were compared. The correlation between the QMG total score minus grip strength score, and three evaluating methods, was analyzed. Results: The grip strength, swallowing, speech, diplopia, ptosis, and facial muscles items showed a clustered distribution. Most patients (94%) presented their maximum grip strength in the first four grip strength measurements. The QMG total score minus the grip strength score had a weak correlation with grip strength decrement (R grip r = 0.276; L grip r = 0.353, both p < 0.05) and moderate correlations with maximum grip strength (R grip r = -0.508; L grip r = -0.507; both p <0.001) and relative grip strength (R grip r = -0.494; L grip r = -0.497, both p <0.001). Conclusions: This study suggests that partial items in the QMGS have low discriminative properties for Chinese populations and the maximum grip strength value is the better method to evaluate grip strength compared to the other two scoring methods. Based on the quartiles of maximum grip strength, we propose new scoring ranges for the grip strength items.